Sharia Mutual Fund Performance, Foreign Ownership and Investment Ability - Siti Saudah; Musdalifah Azis (AFEBI Islamic Finance and Economic Review, 2019)
This study aims to analyze sharia mutual fund performance approaches from the effect of Foreign Ownership and Investment Ability. This research was conducted at equity mutual fund companies listed in Financial Services Ototitas (OJK) for the period 2018-2019. This study used purposive sampling with a total sample of 33 equity mutual funds. The type of data used is quantitative data and the data source is in the form of company annual financial reports. The data analysis tools used were descriptive statistics and panel data regression. The results of this study indicate that Foreign Ownership has a not significant effect on and Investment Ability has a positive and insignificant effect on Mutual Fund Performance.